Sekolah Judicial Review: Strengthening the Legal Culture of Civil Society Organizations in the Indonesian Legal System - Tanto Lailam; Irfan Nur Rachman; Rahmat Muhajir Nugroho; Mukhtar Zuhdy; Rofi Aulia Rahman (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2026)
The research-based legal empowerment program, entitled "Sekolah Judicial Review: Strengthening the Legal Culture for Civil Society Organizations". The objective of this program is to establish community partners as a model of non-state actors who can contribute to the balance of the legal culture of judicial review in Indonesia. The methodological approach employed in this study is anchored in normative and empirical legal research, the Sekolah Judicial Review model approach with a comprehensive curriculum, as well as best practices for non-state actors as petitioners at the Indonesian Constitutional Court. The results of the legal service demonstrated that the Sekolah Judicial Review aims to realize Sustainable Development Goal 16.3. It has enhanced legal knowledge, awareness, compliance, and responsibility among civil society organizations regarding judicial review and national legal systems. The national commitment and responsibility of civil society organizations in the process, decisions, and implementation of judicial review include the following: acting as a balancer of government and political powers; encouraging the realization of an independent and impartial judiciary in deciding judicial review cases; ensuring that the judiciary and justices are not intervened by political, business and other powers; criticizing weak political culture; and encouraging public participation. The recommendation in this legal empowerment program is to strengthen the legal culture of civil society organizations, especially by enabling them to serve as applicants in judicial reviews on specific issues, such as civil and political rights, climate change, and other cases, to strengthen "Peace and Justice Strong Institutions" within the Sustainable Development Goals.